Todos estábamos a la espera de Álvaro Cepeda Samudio edición a cargo de Jacques Gilard - Manuel Guillermo Ortega (Caravelle)
The text contains a review on the critical edition of the story book Todos estábamos a la espera, of the Colombian writer Alvaro Cepeda Samudio, realised by Jacques Gilard and published by Cooperación Editorial, Madrid, 2005. Gilard presents this critical edition in six sections, thus: 1. Introduction, with an intellectual biography of Cepeda Samudio, who lives between the media, the narrative and the cinema, 2. Chronology, that emphasizes the fundamental moments in the life of the author, in relation with the great facts of the History, the world and the Literature, 3. The stories, nine published in the original edition and three stories added by Gilard, 4. Footnotes, with pertinent explanations, mainly, for a reader different from the Colombian, 5. Workcards, and 6. Bibliography commented on Cepeda and its book of stories.